Hewlett-Packard Company : the departure of Mark Hurd (B) - Martin, Kevin; Zheng, Wenhui (Peter); O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
After Mark Hurd steps down as CEO at Hewlett-Packard, Oracle hires him as co-president, as well as a member of their Board of Directors. A day later, Hewlett-Packard files a lawsuit against Hurd alleging he will not be able to do his new job without violating his confidentiality agreement. Tension arises between the two companies, which have been strategic business partners for 25 years. H-P also endures severe criticism from Oracles CEO, Larry Ellison.
Originally published: Martin, K., Zheng, W., & ORourke, J. S. (2010). Hewlett-Packard Company: The departure of Mark Hurd (B). 10-13 (B). Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Hewlett-Packard Company; Oracle Corporation; Computer industry -- Personnel management; Confidential business information